Effects of compound probiotics on intestinal barrier function and caecum microbiota composition of broilers. Issue 5 (3rd September 2022) - Wu, Yunhui; Yang, Fan; Jiang, Wenjuan; Hu, Aiming; Xiong, Zhiwei; Yang, Shuqiu; Cao, Panpan; Cao, Zhanyou; Xiong, Zhonghua; Cao, Huabin
ABSTRACT: Probiotics are beneficial microorganisms existing in nature and animals and can be used in livestock and poultry breeding. Here, 240 1-day-old Arbor Acre (AA) broilers were used to study the effects of compound probiotics (CP) on antioxidant capacity, intestinal barrier function and caecum microorganisms. 2‰, 3‰ or 4‰ CP were added to the basal diet. Blood, jejunum, caecum and caecum contents of broilers were collected on day 60, and the jejunum histopathological observation, oxidative stress state evaluation, intestinal barrier function mRNA level and caecum microflora composition were carried out. The results showed that CP significantly improved the growth performance of broilers in 1-30 days. Moreover, CP supplementation increased superoxide dismutase (SOD) activity, reduced malondialdehyde (MDA) and hydrogen peroxide (H2 O2 ) contents in serum, and increased the mRNA levels of zona occludens 1 (ZO-1), claudin-1 and occludin in the jejunum of broilers. 3‰ CP observably increased the ratio of villus height to crypt depth, and the abundance of the genus Rikenellaceae_RC9_gut_group and Phascolarctobacterium, decreased the abundance of the genus Ruminococcaceae_UCG-014, together with regulation of several genes that are responsible for signaling pathways involved in carbohydrate metabolism, amino acid metabolism and endocrine and metabolic diseases. Taken together, the supplementation of CP could reduce oxidative stress levels, increase the mRNA expression levels of tight junction (TJ)-related genes and the colonization of beneficial bacteria in the caecum, which has a promoting effect on the growth performance in broilers.